Analysis of Application of Cash Receipts Accounting Information System in Improving Internal Control: Analisis Penerapan Sistem Informasi Akuntansi Penerimaan Kas dalam Meningkatkan Internal Control - Rahariyanto, Basya Syafitri; Rahayu, Duwi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the cash receipts accounting information system in improving internal control and assessing whether the activities implemented by PT. Karunia Land has synchronized using the theory of cash receipts accounting information systems and company internal control which can later be used as material for assessment, input, and as suggestions for the development of cash receipts accounting information systems. This study uses qualitative methods through interviews, documentation, and observation. The validity of the data was tested using the technical triangulation method. The analytical techniques used are data reduction, data presentation, and conclusion drawing or verification to analyze cash receipts accounting information system data and analyze internal control at PT. Gift of Land. The results of this study explain that, the application of the accounting information system of PT. Karunia Land does not yet have a flowchart and is effective in accordance with the Standard Operating Procedure (SOP) in terms of cash receipts processes and procedures. Improved internal control of cash receipts accounting information system by PT. Karunia Land as a whole still does not meet the internal control element in terms of organizational structure, there is still a gap between the admin function and the financial function.